Characterization of an intelectin-1 (Itln1) knockout mouse model - Nonnecke, Eric B.; Castillo, Patricia A.; Akahoshi, Douglas T.; Goley, Stephanie M.; Bevins, Charles L.; Lönnerdal, Bo (Frontiers in Immunology, 2022)
Intelectins are carbohydrate-binding proteins implicated in innate immunity and highly conserved across chordate evolution, including both ascidians and humans. Human intelectin-1 (ITLN1) is highly abundant within the intestinal mucosa and binds microbial but not host glycans. Genome-wide association studies identified SNPs in ITLN1 that are linked to susceptibility for Crohn’s disease. Moreover, ITLN1 has been implicated in the pathophysiology of obesity and associated metabolic disease. To gain insight on biological activities of human ITLN1 in vivo, we developed a C57BL/6 mouse model genetically targeting the gene encoding the functional mouse ortholog. In wild-type C57BL/6 mice, both mRNA and protein analysis showed high expression of Itln1 in the small intestine, but manifold lower levels in colon and other extraintestinal tissues. Whereas intestinal expression of human ITLN1 localizes to goblet cells, our data confirm that mouse Itln1 is expressed in Paneth cells. Compared to wild-type littermate controls, mice homozygous for the Itln1 hypomorphic trapping allele had reduced expression levels of Itln1 expression (~10,000-fold). The knockout mice exhibited increased susceptibility in an acute model of experimentally induced colitis with 2% w/v dextran sulfate sodium (DSS). In a model of chronic colitis using a lower dose of DSS (1.5% w/v), which enabled a detailed view of disease activity across a protracted period, no differences were observed in body weight, fecal texture, hemoccult scores, food/water intake, or colon length at necropsy, but there was a statistically significant genotype over time effect for the combined fecal scores of disease activity. In model of diet-induced obesity, using two western-style diets, which varied in amounts of sugar (as sucrose) and saturated fat (as lard), mice with Itln1 ablated expression showed no increased susceptibility, in terms of weight gain, food intake, plasma markers of obesity compared to wildtype littermates. While the mouse genetic knockout model for Itln1 holds promise for elucidating physiological function(s) for mammalian intelectins, results reported here suggest that Itln1, a Paneth cell product in C57BL/6 mice, likely plays a minor role in the pathophysiology of chemically induced colitis or diet-induced obesity.